Productivity analysis using method Murvin E. Mundel case study PT. Johan Sentosa - Ervil, Riko; Rhamadan, Dian Yudistira (Universitas Negeri Padang, 2021)
Productivity is an alternative to evaluating the performance that has been done even one of the most effective ways in assessing the efficiency of using several inputs in producing certain outputs. the study was conducted at PT Johan Sentosa. The company is engaged in processing palm oil into CPO (crude palm oil) and kernels. In this case, the company must replace an important process called the sterilizer system from the horizontal sterilizer to the vertical sterilizer. This change will certainly have an impact on company productivity. In this study, the method used is Marvin E Mundel where partial productivity will be identified in the form of depreciation value index, material, labor, energy, and maintenance, and know the total production value index. The results of this study obtained a partial productivity index on the declining workforce, other partial productivity such as depreciation, material, labor, energy, and maintenance have increased while the index value of total productivity increased after a change in the sterilizer system.